Association between dietary vitamin intake and all-cause mortality in ovarian cancer patients: a prospective cohort study - Ling, Qin; Wu, Linxiang; Xu, Huishan; Zhang, Yang; Chen, Yuying; Sun, Tingting; Zhang, Zuwei; Lai, Huiling; He, Shasha; Yao, Shuzhong; He, Weipeng; Yang, Guofen (Frontiers in Nutrition, 2025)
BackgroundWhile various lifestyle factors have been implicated in cancer prognosis, the role of dietary vitamins in ovarian cancer survival is not well understood. This study aimed to investigate the association between dietary vitamin intake and all-cause mortality in ovarian cancer patients, presenting a potential modifiable avenue for improving outcomes.MethodsData were obtained from 7 consecutive National Health and Nutrition Examination Survey (NHANES) cycles between 2003 and 2016, including 108 ovarian cancer patients. Mortality outcomes were ascertained by matching the National Death Index (NDI). To investigate the association between vitamin consumption and all-cause mortality, multivariate Cox proportional hazards models was employed. Non-linear relationships were further assessed through restricted cubic spline analyses and subgroup analyses were conducted to explore the influence of potential confounders.ResultsA total of 108 ovarian cancer patients were included, of which 24 participants have died. In the adjusted model, higher vitamin A intake was significantly associated with an increased all-cause mortality (HR = 3.826; 95% CI = 1.378–10.627; p = 0.01). In contrast, higher intake of vitamins B1 and B2 was associated with improved survival (HR = 0.234, 95% CI = 0.077–0.71, p = 0.01; HR = 0.14, 95% CI = 0.048–0.408, p < 0.001). Vitamin C intake showed a complex relationship with survival: the highest tertile had an increased risk of death (HRT3 vs. T1 = 4.106; 95% CI = 1.294–13.032; p = 0.017), while the moderate tertile were just the opposite (HRT2 vs. T1 = 0.097; 95% CI = 0.013–0.75; p = 0.025). Non-linear associations were exhibited between vitamins A, B1, and B2 with all-cause mortality (p-non-linear = 0.007, 0.008, 0.027). Subgroup analyses revealed that the education level, racial and smoking status differences may cause difference in results.ConclusionThis study suggests that higher dietary intake of vitamin A may increase mortality risk in ovarian cancer patients, while vitamins B1 and B2 may offer potential survival benefits. The relationship between vitamin C and survival varied with intake levels. These results highlight the potential for personalized dietary interventions in ovarian cancer management.